GRAMMATICAL ERRORS IN INDONESIAN EFL STUDENTS’ WRITING: A LIBRARY RESEARCH FROM THE PERSPECTIVES OF CONTRASTIVE ANALYSIS AND ERROR ANALYSIS - Lili Elisa Rahma; Nazwa Umri Damanik; Rismayani Marpaung; Siti Ismahani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Writing is one of the most challenging skills for learners of English as a Foreign Language (EFL) because it requires the integration of linguistic, cognitive, and communicative competencies. In higher education, writing proficiency is essential for producing various academic texts; however, Indonesian EFL students continue to experience grammatical difficulties that negatively affect the quality of their writing. This study aims to examine the common grammatical errors found in the writing of Indonesian EFL students through the perspectives of Contrastive Analysis and Error Analysis. This study employed a library research design by analyzing and synthesizing relevant books, scholarly journal articles, and previous studies. The findings reveal that the most frequent grammatical errors involve tense usage, subject–verb agreement, articles, prepositions, plural forms, and sentence structure. These errors are primarily attributed to first-language transfer, overgeneralization, incomplete rule application, limited grammatical competence, and structural differences between Indonesian and English. In conclusion, Contrastive Analysis and Error Analysis provide complementary frameworks for identifying the sources of grammatical errors and serve as a valuable basis for improving the writing accuracy of EFL learners. The findings are expected to provide useful insights for teachers, curriculum developers, and researchers in designing more effective EFL writing instruction. ABSTRAK Menulis merupakan salah satu keterampilan yang paling menantang bagi pembelajar Bahasa Inggris sebagai Bahasa Asing (English as a Foreign Language/EFL) karena menuntut penguasaan aspek linguistik, kognitif, dan komunikatif. Dalam pendidikan tinggi, kemampuan menulis sangat penting untuk menghasilkan berbagai karya akademik, namun mahasiswa EFL di Indonesia masih sering melakukan kesalahan gramatikal yang memengaruhi kualitas tulisan. Penelitian ini bertujuan mengkaji kesalahan gramatikal yang umum ditemukan dalam tulisan mahasiswa EFL Indonesia melalui perspektif Analisis Kontrastif (Contrastive Analysis) dan Analisis Kesalahan (Error Analysis). Penelitian ini menggunakan metode kepustakaan (library research) dengan menganalisis berbagai buku, artikel ilmiah, dan hasil penelitian yang relevan. Hasil kajian menunjukkan bahwa kesalahan yang paling dominan meliputi penggunaan tenses, subject–verb agreement, artikel, preposisi, bentuk jamak, dan struktur kalimat. Kesalahan tersebut dipengaruhi oleh transfer bahasa pertama, overgeneralisasi, penerapan aturan yang tidak lengkap, keterbatasan penguasaan tata bahasa, serta perbedaan struktur antara bahasa Indonesia dan bahasa Inggris. Simpulannya, Analisis Kontrastif dan Analisis Kesalahan saling melengkapi dalam mengidentifikasi penyebab kesalahan gramatikal dan dapat menjadi landasan untuk meningkatkan akurasi menulis mahasiswa EFL. Temuan penelitian ini diharapkan menjadi acuan bagi guru, pengembang kurikulum, dan peneliti dalam mengembangkan pembelajaran menulis EFL yang lebih efektif.